Cover Picture. Issue 5 (11th September 2022) - Unknown
Abstract : Inspired by cowpea configuration beneficial to improve rich water transport in arid environment, Wenbo Liu and co‐workers design and construct a monolithic 3D hollow nanoporous CuxO encapsulated mesoporous Cu heterostructure, which shows superior Li storage properties as additive‐free integrated anodes for LIBs. This can be ascribed to the synergistic effect between interconnected hollow CuxO nanotubes and internal mesoporous Cu conductive network, indicative of its promising application toward advanced LIBs. Abstract : Inspired by cowpea configuration beneficial to improve rich water transport in arid environment, Wenbo Liu and co‐workers design and construct a monolithic 3D hollow nanoporous CuxO encapsulated mesoporous Cu heterostructure, which shows superior Li storage properties as additive‐free integrated anodes for LIBs. This can be ascribed to the synergistic effect between interconnected hollow CuxO nanotubes and internal mesoporous Cu conductive network, indicative of its promising application toward advanced LIBs.